2009
DOI: 10.1111/j.1443-1661.2009.00901.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Thin Endoscopic Method of Transanal Drainage Tube Insertion for Acute Colonic Obstruction Due to Colorectal Cancer

Abstract: Aim: Insertion of a transanal drainage tube is effective in the management of obstructing colorectal cancer.We devised a new method of inserting the transanal drainage tube safely and quickly using a thin endoscope.Methods: Sixteen patients (7 men and 9 women) with obstructive left-sided colorectal cancer were treated by inserting a transanal drainage tube using a thin endoscope. We inserted a transanal drainage tube for 32 patients (21 men and 11 women) of left-sided colorectal cancer by conventional method.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The good results obtained with obstruction due to anastomotic stricture suggest that this is an excellent indication for transanal drainage tube placement. Ohnita et al reported a method of transanal tube insertion using a thin endoscope [19]. We used this method successfully in one patient (No.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The good results obtained with obstruction due to anastomotic stricture suggest that this is an excellent indication for transanal drainage tube placement. Ohnita et al reported a method of transanal tube insertion using a thin endoscope [19]. We used this method successfully in one patient (No.…”
Section: Discussionmentioning
confidence: 93%
“…Ohnita et al. reported a method of transanal tube insertion using a thin endoscope [19]. We used this method successfully in one patient (No.…”
Section: Discussionmentioning
confidence: 99%
“…The internal diameter of a dilated SEMS is in the range of 18–25 mm [ 53 ]. DT, with an internal diameter of about 7 mm, is fixed by an inflated balloon catheter before the obstructive lesion [ 54 ]. The application of SEMS or DT as a BTS effectively relieves symptoms in patients with colorectal cancer obstruction, avoiding the need for emergency surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The primary option for colorectal cancer patients is surgery. For right-sided colonic cancer obstruction or chronic partial obstruction, stage 1 whole resection and anastomosis is preferred following sufficient preoperative bowel preparation (9,10). …”
Section: Discussionmentioning
confidence: 99%